Self‐Polymerized Disordered Carbon Enabling High Sodium Storage Performance through Expanded Interlayer Spacing by Bound Sulfur Atoms. Issue 21 (23rd August 2018) - Li, Wei; Wang, Kangli; Cheng, Shijie; Jiang, Kai
Abstract: An effective strategy to fabricate sulfur‐doped carbon with tunable doping sites is developed using a one‐step pyrolytic technique. Applied as Na‐storage anode, this sulfur‐doped carbon exhibits high reversible capacity, excellent rate capability (330 mAh g −1 at 0.02 A g −1 and 158 mAh g −1 at 5 A g −1 ), as well as superior durability (159 mAh g −1 over 10000 cycles at 2 A g −1 with 95.7 % retention). Experimental characterization and theoretical calculation reveal that interlayer C−S−C bonds not only expand the d002 spacing, but also provide an alternative pathway for electron transport. This improves Na + ion intercalation/deintercalation capability and electronic conductivity. Abstract : Unique interlayer C‐S‐C bonds in sulfur‐doped carbon are not only enhancing Na + ion uptake and removal by expanding the interlayer distance of the (002) planes, but are also providing electron transport bridges to increase the electronic conductivity. The C−S−C bonds are thereby greatly improving the reversible Na‐storage capacity as well as the fast charge/discharge capability of the disordered S‐doped carbon anodes in sodium‐ion batteries.